Trichoscopic Features of Syphilitic Alopecia and Alopecia Areata: A Comparative Study - Tejapira K; Sakpuwadol N; Pomsoong C; Ratanapokasatit Y; Suchonwanit P (Dove Medical Press, 2023)
Kasama Tejapira, Nawara Sakpuwadol, Cherrin Pomsoong, Yanisa Ratanapokasatit, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 ext 4, Email poonkiat@hotmail.comBackground: Syphilitic alopecia (SA) and alopecia areata (AA) are two distinct conditions that frequently present diagnostic difficulties, especially when differentiating between them due to their similar clinical presentations. Trichoscopy may help in differential diagnosis, but a comparison between trichoscopic features of SA and AA is yet to be researched.Objective: To compare trichoscopic features between SA and AA and determine their discriminative values.Methods: Electronic medical records and trichoscopic images of patients diagnosed with SA or AA between January 2000 and February 2022 were retrieved. Trichoscopic features were statistically compared, and their discriminative values were demonstrated as sensitivity, specificity, predictive value, likelihood ratio, and area under the receiver operating characteristic curve (AUC).Results: A total of 69 patients were included: 23 SA and 46 AA cases were matched with a 1:2 ratio. Black dots, broken hairs, pigtail hairs, exclamation mark hairs, tapered hairs, angulated hairs, and non-pigmented regrowing hairs were significantly more prevalent in AA than in SA (all P< 0.05), whereas erythematous background was more prevalent in SA than in AA patients (P=0.008). Among the aforementioned trichoscopic features, exclamation mark hairs and non-pigmented regrowing hairs had a high positive likelihood ratio for AA (16.17 and 8.34, respectively); however, only exclamation mark hairs revealed high AUC (AUC=0.816).Conclusion: Despite the presence of several similar trichoscopic features between SA and AA, trichoscopy can aid in distinguishing between the two diseases. Exclamation mark hairs are the only trichoscopic feature that can be used to differentiate patients with clinically suspicious SA from those with AA.Keywords: alopecia areata, alopecia syphilitica, dermoscopy, exclamation mark hairs, syphilis, trichoscopy